Desain Interior Perpustakaan Universitas Indonesia dalam Persepsi Pemustaka - Ayu Sakirah Chaniago, Winda; Hayati, Nurul (UI Scholars Hub, 2024)
This study is motivated by the futuristic interior design and attractive facilities of the University of Indonesia (UI) Library, which create a comfortable environment. However, statistical data show a significant decline in student visits between September and December 2023. This phenomenon raises questions about the factors influencing users' experiences, particularly their perceptions of the library's interior design, which should ideally enhance comfort and increase visitation. This research is essential to understand how interior design affects user perception and visit rates, and to provide recommendations for improvements that could boost the library's appeal among students. This study employs a descriptive method with a quantitative approach. Data were collected through questionnaires, observations, literature review, and documentation. The population consists of 15,190 student users of UI Library, and based on Isaac and Michael's formula, a sample of 284 respondents was obtained. Accidental sampling was used as the sampling technique. The results show that users' perceptions of the interior design elements averaged 3, while the interior design principles received an average score of 3.33. Overall, the users' perception of the library's interior design averaged 3.29, falling within the